2022
DOI: 10.1039/d1ra08454b
|View full text |Cite
|
Sign up to set email alerts
|

NiIINPs entrapped within a matrix ofl-glutamic acid cross-linked chitosan supported on magnetic carboxylic acid-functionalized multi-walled carbon nanotube: a new and efficient multi-task catalytic system for the green one-pot synthesis of diverse heterocyclic frameworks

Abstract: In this research work, an Fe3O4/f-MWCNT-CS-Glu/NiII hybrid nanocomposite was synthesized, characterized, and used as a new and efficient multi-task catalytic system for the green one-pot synthesis of diverse heterocyclic frameworks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 200 publications
0
6
0
Order By: Relevance
“…In continuation of our interest in the synthesis of heterocyclic compounds using MCRs in the presence of noncatalytic systems, 77 herein, an active, efficient, and magnetic nanocomposite system for the synthesis of benzodiazepine derivatives via a one-pot three-component condensation reaction of o -phenylenediamine ( 1 ), dimedone ( 2 ), and various aliphatic/aromatic/heteroaromatic aldehydes ( 3a–o ) is introduced. In this regard, to prepare this new nanocomposite system, first the pristine carboxylic acid functionalized multi-walled carbon nanotubes (f-MWCNTs) were magnetized through the chemical co-precipitation of Fe 2+ and Fe 3+ in an alkaline solution.…”
Section: Resultsmentioning
confidence: 99%
“…In continuation of our interest in the synthesis of heterocyclic compounds using MCRs in the presence of noncatalytic systems, 77 herein, an active, efficient, and magnetic nanocomposite system for the synthesis of benzodiazepine derivatives via a one-pot three-component condensation reaction of o -phenylenediamine ( 1 ), dimedone ( 2 ), and various aliphatic/aromatic/heteroaromatic aldehydes ( 3a–o ) is introduced. In this regard, to prepare this new nanocomposite system, first the pristine carboxylic acid functionalized multi-walled carbon nanotubes (f-MWCNTs) were magnetized through the chemical co-precipitation of Fe 2+ and Fe 3+ in an alkaline solution.…”
Section: Resultsmentioning
confidence: 99%
“…Mousavi et al reported the synthesis of coumarins catalysed by cockscomb flower-like nanocomposites (Fe 3 O 4 @SiO 2 @KCC@MPTMS@Cu II ; Scheme 43 ) 96 for the pseudo-three-component synthesis of bis-coumarins ( 146 ), without using solvent, from substituted benzaldehyde ( 47 ) and 4-hydroxycoumarin ( 46 ). The novel catalysts were recovered and reused in up to seven runs without significant loss in activity.…”
Section: Aza- and Oxa-heterocycle Synthesis Catalysed By Mnpsmentioning
confidence: 99%
“…92 Therefore, synthesis of 2,3-dihydroquinazoline derivatives has attracted the attention of organic and pharmaceutical chemists, leading to various methods for the preparation of 2,3-dihydroquinazoline derivatives in order to achieve higher reaction efficiency. 70,93–105 Most of these reported methods have disadvantages such as multi-stage preparation methods, long reaction time, low efficiency, hard reaction conditions, and the use of precious metals or toxic reagents. Thus, using new methods for the synthesis of 2,3-dihydroquinazolines under desired reaction conditions is important.…”
Section: Introductionmentioning
confidence: 99%
“…68 Therefore, chitosan application as a new support material for heterogeneous catalysis is increasing. 69,70 Also, the use of ligands containing multi-amine groups in a chain or dendrimer increases the catalytic efficiency by increasing the number of active sites.…”
Section: Introductionmentioning
confidence: 99%